REDESIGN SUMUR SUCKER ROD PUMP MENGGUNAKAN METODE ELECTRICAL SUBMERSIBLE PUMP SEBAGAI ARTIFICIAL LIFT PADA LAPANGAN Y - Nursitna F. R. Mahmud; Kristofol Waas; Leslie. S. Loppies (Department of Mechanical Engineering, 2023)
Natural resources found in the pores of rocks and beneath the earth's surface include oil and gas. In the oil and gas industry, when initial conditions are stable, the pressure within the reservoir can naturally push the fluid to surface. Once a well is drilled through the reservoir and put into production, there is a pressure drop around the borehole, prompting the use of artificial lift methods. Artificial lift is used to assist process of lifting fluid from the bottom of the well to surface. Well X was no longer able to produce naturally and had an SRP. There is a decline in production during production process. Gross up program can be conducted to prevent the decline in production capacity and oil production rate from the well. Gross up is a program to increase the gross production rate by converting SRP to ESP. The objective is to calculate the evaluation of the artificial lift installed in the form of an ESP. The calculations performed include oil reserves, well X performance, using pipesim software with tubing ID, operating frequency, and stage parameters. The conclusion of this research is that the installed artificial lift, namely the ESP pump, is optimal based on pump performance. Keywords: Artificial lift Method; ID Tubing; Stages; Operating Frequency